HEAVY CHAIN SUBCLASSES OF HUMAN γG-GLOBULIN : SERUM DISTRIBUTION AND CELLULAR LOCALIZATION - Bernier, G. M. (The Rockefeller University Press, 1967)
Two antigenic types of naturally occurring proteins related to the papain produced F(c) fragment of γG-globulin have been studied. Most normal and myeloma γG-globulins are related to one or the other of these proteins, based on antigenic and structural characteristics of their heavy chain. Molecules bearing the determinant "Cr" are approximately 10 times as abundant as those bearing the determinant termed "Zu" in pools of normal γG-globulin and among a large group of γG-myeloma globulins. Both populations have properties of typical γG-globulin antibodies. Splenic cells, stained for these two populations with specific fluorescent antibody preparations, are found to contain one or the other of the two populations of γG-globulin, but not both. Approximately 10 times as many cells contain the Cr determinant as contain the Zu determinant.